4‐Dimethylaminopyridine‐Catalyzed Regioselective [3+2] Cycloaddition of Isatin‐Derived Morita−Baylis−Hillman Adducts with Azo Esters: A Simple Protocol to Access 3‐Spiropyrazole‐2‐oxindoles. Issue 16 (4th July 2018) - Ren, Yue; Meng, Ling‐Guo; Peng, Tao; Zhu, Lijuan; Wang, Lei
Abstract: An efficient and regioselective 4‐dimethylaminopyridine catalyzed [3+2] cycloaddition of isatin‐derived Morita−Baylis−Hillman adducts with azo esters was developed for the construction of 3‐spiropyrazole‐2‐oxindoles. This protocol generated the desired spiropyrazoles in good to excellent yields with good functional group compatibility under mild reaction conditions. Abstract :